2021
DOI: 10.1038/s41598-021-98386-x
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic aromatic hydrocarbons in the snow cover of the northern city agglomeration

Abstract: Sixteen priority polycyclic aromatic hydrocarbons (PAHs) were qualitatively and quantitatively assessed by high-performance liquid chromatography with fluorescence detection in snow samples collected at 46 sites of Arkhangelsk as a world’s largest city above 64 degrees north latitude. The average, maximum and minimum PAH concentrations in snow were 168, 665, and 16 ng/kg, respectively. The average toxic equivalent value in benzo(a)pyrene units was 3.6 ng/kg, which is three-fold lower than the established maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Moreover, the removal from the water column of the heavier PAHs via vertical particle settling, particularly in the shallower coastal shelf seas might also contributed to the reduced net southerly outflow from the Arctic of heavier PAHs (relative to the lighter PAHs). To a lesser extent, the longer retention of more hydrophobic/heavier PAHs in melting snow/sea ice might be another possible explanation for their reduced net southerly outflow, although large parts of the Arctic Ocean are now dominated by single season ice (rather than multi‐year ice) (Kozhevnikov et al., 2021; Pawlak et al., 2021). The molecular weight‐dependent net transport of PAHs we observed was similar with those for PFASs, as a net southward transport for short‐chain PFAS, while a net northward transport for the PFASs with ≥8 perfluorinated carbon atoms (Joerss et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the removal from the water column of the heavier PAHs via vertical particle settling, particularly in the shallower coastal shelf seas might also contributed to the reduced net southerly outflow from the Arctic of heavier PAHs (relative to the lighter PAHs). To a lesser extent, the longer retention of more hydrophobic/heavier PAHs in melting snow/sea ice might be another possible explanation for their reduced net southerly outflow, although large parts of the Arctic Ocean are now dominated by single season ice (rather than multi‐year ice) (Kozhevnikov et al., 2021; Pawlak et al., 2021). The molecular weight‐dependent net transport of PAHs we observed was similar with those for PFASs, as a net southward transport for short‐chain PFAS, while a net northward transport for the PFASs with ≥8 perfluorinated carbon atoms (Joerss et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Among large Arctic rivers (Yenisei, Ob, Lena, Kolyma, Pechora) the Northern Dvina River takes a special place due to the presence of densely populated areas in its delta. The presence of the developed pulp and paper industry, shipbuilding factories, power generation plants, and large river/seaports leads to significant emissions of microplastics [20]. A recent study showed that the Northern Dvina River may be considered a major source of microplastic pollution of the White Sea [21], and therefore, the entire Arctic region.…”
Section: Introductionmentioning
confidence: 99%